Felis catus Papillomavirus Types 1, 2, 3, 4, and 5 in Feline Bowenoid in Situ Carcinoma: An In Situ Hybridization Study. Issue 6 (November 2019) - Vascellari, Marta; Mazzei, Maurizio; Zanardello, Claudia; Melchiotti, Erica; Albanese, Francesco; Forzan, Mario; Croce, Marta Francesca; Alberti, Alberto; Abramo, Francesca
Several studies based on histopathology or molecular investigations suggest a causal relation between Felis catus papillomavirus (FcaPV-2) infection and bowenoid in situ carcinoma (BISC) in cats. Nevertheless, data on distribution of viral DNA for different F. catus papillomavirus types (FcaPV-1, 2, 3, 4, 5) in precancerous skin lesions are lacking. In this study, incisional and excisional skin biopsies from 18 cats with BISC were investigated for the presence of FcaPV DNA by quantitative polymerase chain reaction (qPCR) and chromogenic in situ hybridization (CISH) using specific probes to detect each of the FcaPVs that have been identified so far. By qPCR analysis, 15 of 18 samples were positive for FcaPV-2, 2 were positive for FcaPV-4, and 1 sample was negative for all FcaPVs studied. Two cases were positive for FcaPV-5 by qPCR only. FcaPV-1 and FcaPV-3 were not detected by either method. CISH positivity for FcaPV-2 and FcaPV-4 was 100% concordant with qPCR. FcaPV-2 CISH signal was observed as nuclear dots within grouped neoplastic keratinocytes in 12 BISCs and in the perilesional skin of 9 biopsies. In 3 of these 9 cases, the signal was not observed within the BISC. FcaPV-4 CISH positivity was detected only within BISCs in 2 cases. The overall rate of concordance for FcaPV detection between PCR and CISH was 97.8%. This study suggests that CISH is a reliable method to detect FcaPV-2 and FcaPV-4 infection in cats and provides useful information on the type, rate, and localization of infected cells.